Lamòling Bèaka: immanence, rituals, and sacred objects in an unwritten legend in Alor - Perono Cacciafoco, Francesco (2018)
This paper recounts a parallel story of the Lamòling myth. The original analysis of the legend addressed the relationship between two gods, Lamòling and Lahatàla, from the Abui traditional religion. The myth evolved from ancestral times to the arrival of Christianity in Alor, with the resultant association of the ‘bad’ god as a demon and, finally, as the devil. This paper completes the myth as handed down from traditional ‘owners’ of the narrative and storytellers by telling a parallel version centered around an Abui ‘prophet’, Fanny, who was the only person able to travel to Lamòling Bèaka, ‘the land of the Lamòling gods/servants’. We also focus on a number of sacred objects and rituals associated with this religious myth and on their symbolic meaning for the Abui. This account tells a different version of the killing and eating of an Abui child by these gods/supernatural entities and of how Fanny came upon the gruesome feast. The paradoxical absence of Lamòling in this version of the myth depicts him as an immanent being, pervading and sustaining all that is real and created in nature, existing anywhere and nowhere at the same time.